Reproduction of the Collared Lemming, Dicrostonyx Groenlandicus - Hasler, John Frederick (1974)
Made available in DSpace on 2014-12-12T01:27:45Z (GMT). No. of bitstreams: 1 7500321.pdf: 9746824 bytes, checksum: 367513b27118e785e44e9e9b70955e6c (MD5) Previous issue date: 1974 Embargo set by: Seth Robbins for item 65680 Lift date: Forever Reason: Restricted to the U of I community idenfinitely during batch ingest of legacy ETDs Restricted to the U of I community idenfinitely during batch ingest of legacy ETDs U of I Only 266 p. Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 1974.